A historical appreciation of the nexus between the colonial African elite -nationalist cleavages and the elusive conflict resolution and national healing efforts in post-colonial Zimbabwe, 1960-2011 - Tarugarira, Gilbert (Midlands State University Press, 2016)
There are many factors that explain the birth of ethnic-based conflict in Zimbabwe. Colonial rule's divide and rule practices of governance and the confrontational anti-colonial nationalisms of the 1960s and 1970s have continued to reproduce and nurture intractable conflict have often been kept alive by people who want to keep such conflict in the post-colonial State. These historical roots of conflict have often been kept alive by people who want to keep such conflict alive. The political elites, for example, have frequently magnified the importance of historical animosities for their own gain. This study considers the elite to be the educated that spearhead the struggle against colonialism and continued upon the granting of independence to be in control of the major institutions of power in Zimbabwe. By playing to long-standing fears and resentments among their own power and legitimacy. Conflicts are an intrinsic, inevitable and unavoidable aspect of social change and human interaction. As such, they can play a positive role in acting as a springboard for social change and means of promoting justice and peace while...